Analisa Tingkat Pelayanan Lalu Lintas pada Simpang Tiga Jalan Sudanco Supriadi Kecamatan Sukun Kota Malang - Mendonca , Oscar De ; Arifianto, Andy Kristafi ; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Malang City is the second largest city in East Java Province with an area of ??110.06 km2, after Surabaya City, with a population of 895,387wawa (2017) with an increase of 3.9% annually. Population growth which continues to increase every year along with the use of transportation which increases every year. With the faster growth of traffic, it must be balanced with an increase in adequate transportation facilities so that the roads do not cause obstacles and congestion. One of the areas affected by traffic growth is at Jalan Sudanco Supriadi, Sukun sub-district, Malang City. The purpose of this study was to find out some important things including characteristics, road capacity, road service level and finally to find out the capacity and level of road service for 5 years. To obtain traffic data, a traffic survey is conducted. Then the data is processed so as to produce (LHR) in the first week is greater than the second week with the first week number of 2782.5smp / hour and the second week of 2740.2 junior / hour, thecapacity C of the intersection of three corners of supriadi in 2018 is amounting to 2578.68 pcu / hour, while the prediction of capacity in the next 5 years is 4481.2smp / hour, the level of road service for the next 5 years F is very low.